Fire resistant glass fabric-epoxy composites with reduced smoke emission - Oliwa, Rafał; Oleksy, Mariusz; Oliwa, Joanna; Węgier, Aleksandra; Krauze, Sławomir; Kowalski, Maciej (Polimery, 2021)
In this article a preparation method of epoxy resin/glass fabric composites with reduced flammability and smoke emission was presented. For this purpose the two groups of powder-epoxy compositions containing: (1) melamine polyphosphate (MPP) and aluminum diethyl phosphinate (AlDPi); (2) ammonium polyphosphate (APP) and dipentaerythritol (DPE) were used as matrices in six-ply glass fabric reinforced composites. The flame retardants content was 25 wt %. In addition, the 10–15 wt % of zinc borate (ZB) as a smoke reducing agent was added to each compositions. The flame resistant and smoke emission of prepared laminates designed for application in public transport components were evaluated. It was found that with the increase of zinc borate content, the emission of fumes decreased. The lowest maximum of specific optical density (Dsmax = 312.2), specific optical density in the first 4 minutes of the test [Ds(4) = 304.1] and cumulative specific optical densities in the first 4 minutes of the test (VOF4 = 707.6 min) have been achieved for composite containing 10 wt % of MPP, 15 wt % of AlDPi and 15 wt % of ZB. Furthermore, this composite was characterized by V0 class by UL94 test, limiting oxygen index LOI = 36.8 % and maximum average rate of heat emission MAHRE = 80 kW/m2.